2013
DOI: 10.1007/s00261-013-0038-0
|View full text |Cite
|
Sign up to set email alerts
|

Diffusion-weighted MRI in bladder carcinoma: the differentiation between tumor recurrence and benign changes after resection

Abstract: DWI is superior to DCE MRI for differentiating recurrent bladder tumors from postoperative inflammation or fibrosis. DWI can be included in the follow-up MRI protocol after bladder cancer surgery.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
75
0
6

Year Published

2013
2013
2020
2020

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 76 publications
(81 citation statements)
references
References 19 publications
0
75
0
6
Order By: Relevance
“…This is because several studies in different cancers suggest that DWI may, contrary to standard morphologic MRI, be potentially able to distinguish between residual tumor tissue and non-neoplastic residual changes (e.g., fibrosis) after therapy (8)(9)(10)(11)(12).…”
Section: Introductionmentioning
confidence: 99%
“…This is because several studies in different cancers suggest that DWI may, contrary to standard morphologic MRI, be potentially able to distinguish between residual tumor tissue and non-neoplastic residual changes (e.g., fibrosis) after therapy (8)(9)(10)(11)(12).…”
Section: Introductionmentioning
confidence: 99%
“…Notably, several recent, smaller-sized studies suggest that DWI-MRI may-similar to 18F-FDG-PET/CT, and unlike standard morphologic MRI or CE-CT-possibly be able to distinguish between vital tumor tissue and residual changes (e.g., fibrosis) after therapy (13)(14)(15)(16)(17). The data that support the notion that DWI-MRI is comparable with 18F-FDG-PET/CT for lymphoma staging are, however, mainly based on patients with diffuse large B-cell lymphoma (DLBCL) and Hodgkin lymphoma, and/or a limited sample size (18)(19)(20)(21).…”
Section: Introductionmentioning
confidence: 99%
“…The successfully clinical application of DW-MRI is based on the principle that, through random and diffusion-driven displacement by water molecules, live tissue structures can be probed at a microscopic scale, which is beyond the imaging resolution of other methods [11]. In multiple previous studies, DW-MRI showed excellent performance in accurate characterization of lesions, and the results correlated with histological grading, clinical and pathological staging, differentiating tumour recurrence and guiding correct treatment decision in BC, and the staging accuracy was 96%, with a high diagnosis accuracy of 93.65% [9,[12][13][14][15]. Nevertheless, other studies showed that there is not enough evidence to suggest a high diagnostic performance of DW-MRI, especially in early and accurate detection of BC [16].…”
mentioning
confidence: 97%